Spanish in Pucará: Concordance - Olaechea Monge, Christian Rodolfo (2002)
Aspects of agreement in the Spanish spoken in the district of Pucará are studied. town located in the province of Huancayo (Junín-Perú). Agreement, as a syntactic category, presents peculiar characteristics such as. product of the influence of the Quechua language, which is reflected both in the hybridizations and in the hypercorrections manifested by the speakers of this central area of the country.